Selection of lines of Valeriana jatamansi Jones, a high value medicinal plant in North Eastern Himalayan region - Chakraborty, Soumendra; Mukherjee, Dhiman; Baskey, Sibdas (The Indian Journal of Genetics and Plant Breeding, 2016)
Valeriana jatamansi Jones, newly introduced endangered medicinal plant in north eastern Himalayan region from North Sikkim (Sangtok 27.25°N 88.31°E) to the hilly region of West Bengal (Kalimpong 27.06°N 88.47°E) was conserved in field gene banks in Kalimpong regional research station for its highly active medicinal properties. Morphological characterization and selection of 9 lines on the basis of leaf margin and time of flowering was done in the field gene banks maintained at Kalimpong. Three types of plant phenotype namely, entire, sinuate and wavy was selected along with morphological traits to find the overall performance of the lines in the plant population.